The Influence of Health Promotion Animation Videos on Students' Knowledge of Sexual Violence Prevention - Widodo, Riyo (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: The main objective of this study was to determine the effect of using animated videos in health promotion related to the prevention of sexual violence is to increase students' knowledge and awareness of the dangers of sexual violence and preventive measures. Methodology: This study uses a quantitative research type with a quasi-experimental design involving an experimental group and a control group. The population in this study were fifth grade elementary school students. The data collection technique in this study used a questionnaire method distributed students before and after health promotion intervention. The collected data were analyzed using descriptive and inferential statistical techniques. Main Findings: This study successfully showed that animated videos as a health promotion media are effective in improving the knowledge and attitudes of high school students regarding the prevention of sexual violence. Compared with traditional methods such as power point, animated videos are more able to attract attention and improve students' understanding, resulting in a significant increase in their knowledge and attitudes towards this sensitive topic. Novelty/Originality of this study: The novelty of this study lies in the use of animated videos as an innovative and interesting health promotion media to improve the knowledge and attitudes of high school students regarding the prevention of sexual violence. This study introduces a dynamic and interactive visual approach, different from conventional methods such as lectures or the use of power point.